Governance and Failure: On the Limits of Sociology: z wprowadzeniem Boba Jessopa - Malpas, Jeff; Wickham, Gary (Journal of Public Governance, 2010)
Failure is an ubiquitous and central feature of social life. Yet much sociological inquiry focuses not on failure but on success. This paper adopts a sceptical approach to sociological theory, advancing an account of the necessary limits of sociological inquiry and defending the idea of the primacy of failure on two fronts: first, through the examination of a sociological approach currently developing around the Foucaultian idea of ‘governmentality’; and second, through a more general philosophical consideration of the connections between failure and practices of governance or control.